THE DYNAMICS OF JUDICIAL POWER AND THE IMPLEMENTATION OF THE RULE OF LAW PRINCIPLES IN INDONESIA - Yafet Wambrauw; Manase Tabuni; Obet Nawipa; Samuel Kogoya (International Journal of Education and Social Science Studies, 2025)
This article examines the evolving dynamics of judicial power and their implications for the implementation of the rule of law principle in Indonesia. The study specifically addresses the persistent gap between the normative guarantees of judicial independence and access to justice, and their practical realization within Indonesia’s legal and political framework. Employing a combined normative and empirical approach, the research analyzes constitutional and statutory provisions, key Constitutional Court decisions, and the implementation of legal aid programs, particularly those targeting vulnerable groups such as low-income communities and persons with disabilities. Empirical insights were derived from documentary analysis and secondary data related to judicial reform initiatives. The findings reveal that although the legal framework has strengthened the formal autonomy of the judiciary, structural constraints, political interventions, and administrative inefficiencies continue to undermine its independence and the equitable enforcement of justice. These obstacles not only affect the impartiality of judicial decision-making but also challenge public trust and the legitimacy of judicial institutions. Drawing on theories of rule of law and judicial independence, the study argues that a substantive realization of the rule of law in Indonesia requires more than normative affirmation; it demands institutional reform, transparent judicial appointments, and participatory oversight mechanisms. This research contributes to constitutional law scholarship by offering a comprehensive analysis of the interplay between judicial power, political structures, and access to justice, while proposing a reform-oriented framework for strengthening the judiciary’s role in upholding a democratic and equitable rule of law in Indonesia.